Material flow in heterogeneous friction stir welding of thin aluminium sheets: Effect of shoulder geometry - Leal, R. M. (2008)
http://www.sciencedirect.com/science/article/B6TXD-4T8HHG4-4/2/0b8e12809caaa618052d7b27494c16ac